2023
DOI: 10.3390/plants12162891
|View full text |Cite
|
Sign up to set email alerts
|

Affecting Factors of Plant Phyllosphere Microbial Community and Their Responses to Climatic Warming—A Review

Abstract: Phyllosphere microorganisms are not only an important part of plants, but also an important part of microorganisms. In this review, the function of phyllosphere microorganisms, the assembly mechanism of phyllosphere microorganisms, the driving factors of phyllosphere microbial community structure, and the effects of climate warming on phyllosphere microbial community structure were reviewed. Generally, phyllosphere microorganisms have a variety of functions (e.g., fixing nitrogen, promoting plant growth). Alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
(229 reference statements)
0
6
0
Order By: Relevance
“…The growth of phyllosphere microorganisms depends on the nitrogen and phosphorus contents which are in turn governed by the physical and chemical properties of the soil. The soil's microbial population serves as a crucial storage reservoir for phyllosphere microorganisms [ 34 ]. Therefore, it appears that identification of individual microorganisms present in tea grades collected from different elevations and/or agro-climatic regions might be useful to some extent to assess the variations in physical and chemical quality of the final tea grades.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of phyllosphere microorganisms depends on the nitrogen and phosphorus contents which are in turn governed by the physical and chemical properties of the soil. The soil's microbial population serves as a crucial storage reservoir for phyllosphere microorganisms [ 34 ]. Therefore, it appears that identification of individual microorganisms present in tea grades collected from different elevations and/or agro-climatic regions might be useful to some extent to assess the variations in physical and chemical quality of the final tea grades.…”
Section: Resultsmentioning
confidence: 99%
“…Related studies on olive’s phyllosphere have identified bacteria from the Proteobacteria, Firmicutes and Actinobacteria phyla [ 34 ]. Other studies with different crops have found that Methalobacterium , Pseudomonas and Sphingomonas genera were predominant [ 35 ]. When all fourteen microorganisms were tested in in vitro inhibition assays against H. vastatrix , only three were able to inhibit rust germination effectively, similar to the chemical control.…”
Section: Discussionmentioning
confidence: 99%
“…The advancing climate change is expected to cause a shift in the population of pathogenic fungi in crop plants [ 7 , 61 , 62 ]. Fusarium infestation will likely decrease, as they require constant high moisture for their development [ 6 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wheat ( Triticum aestivum L.) is one of the most economically important crops in the world [ 3 ], but unfavorably, wheat is highly susceptible to fungal infections. Fusarium and Alternaria fungi are responsible for prominent infections of various crops, including summer and winter wheat [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%